Multiply Fun: Media Game Digital Berbasis Roblox Studio untuk Pembelajaran Perkalian di Kelas V - Michael Edtrianda Desveron; Khusnul Khotimah (Mataram University, 2026)
The rapid development of digital technology has created a need for innovative learning media that can optimize elementary school students' participation and understanding, particularly in mathematics education. However, the teaching of multiplication properties is still predominantly carried out using conventional methods, which tend to be less engaging and contribute to students' low learning interest. This study aimed to develop and evaluate the feasibility of an interactive digital game-based learning media using Roblox Studio for teaching the properties of multiplication. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation questionnaires covering media, content, and language aspects, as well as response questionnaires completed by teachers and students. The findings revealed that the developed learning media achieved a very high level of feasibility and received positive responses from both teachers and students. Therefore, the Roblox Studio-based learning media is considered suitable as an alternative interactive and engaging medium for mathematics learning in elementary schools.